Tinjauan Yuridis Tentang Tanggungjawab Hukum Terhadap Pelaksanaan Perjanjian Sewa Menyewa Mobil - PRANOTO, DARUDRIYO JATI; , Nuswardani, S.H., S.U (2017)
This study aims to determine the form of the agreement and implementation of rules, rights and obligations under the lease agreement the car on the CV. Kartika Puri and accountability in the tenancy agreement in CV. Kartika Putri. The research method uses juridical-normative research with qualitative descriptive analysis. The results showed that the shape of the car rental agreement made with raw form (standard) one-sided, with the strong position that the CV. Kartika Putri to the agreement. Regarding the implementation of rules, rights and obligations is an agreement, after the tenant pay the rent and the lessor handed enjoyment of the goods, then when it has occurred tenancy agreement between the two sides, then the treaty is valid according to the law valid and enforceable as it should, while the shape responsibility CV. Kartika Puri when not experiencing such breach can not provide cars to order, then the CV. Kartika Puri replace with other similar cars wearing half the rental price of the normal price.